Sewage sludge as a sustainable feedstock for biodiesel: Advances in conversion technologies and catalytic applications - Christopher Selvam D; Yuvarajan Devarajan; Raja T (Results in Engineering)
The conversion of sewage sludge into biodiesel presents a sustainable approach to waste management while simultaneously advancing renewable energy objectives. Sewage sludge, possessing a lipid content ranging from 10 % to 25 %, serves as a cost-effective raw material for biodiesel synthesis, thereby adhering to the tenets of circular economy principles. This review delves into sophisticated conversion methodologies, including transesterification, pyrolysis, and hydrothermal liquefaction (HTL), emphasizing their efficacy and yield. Supported heteropolyacids (HPAs), notably phosphotungstic and phosphomolybdic acids when deposited on silica and alumina, exhibit remarkable catalytic efficiency, attaining biodiesel yields of 90 % to 95 % under optimized operational parameters. HTL techniques yield bio-oil outputs of 45 % to 60 %, establishing it as one of the most proficient approaches for sludge conversion. Furthermore, the incorporation of supported HPAs enhances reaction kinetics, diminishes byproduct formation, and facilitates the reusability of catalysts for 5 to 6 cycles, thereby reducing both costs and environmental repercussions. The techno-economic evaluation indicates production expenses as low as $0.50 to $0.70 per liter, while life-cycle assessments suggest a decrease in CO₂ emissions of up to 80 % in comparison to traditional diesel. This review elucidates existing obstacles, such as feedstock heterogeneity and catalyst longevity, and advocates for subsequent research aimed at optimizing sludge-to-biodiesel conversion technologies for implementation at a large scale. By offering detailed methodologies and quantitative insights, this investigation contributes to the body of knowledge in sustainable energy production and waste valorization.